(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Blockchain technology has the potential to significantly alter our corporate environment and will be very influential over the next few decades. It has the potential to alter our economic structure and the way we see corporate operations. Since it cannot be altered or falsified, blockchain is a decentralized and distributed ledger system that attempts to provide transparency, data security, and integrity. Only a small portion of current research on blockchain technology is geared toward examining its use in contexts or industries other than cryptocurrencies like Bitcoin. The majority of current research on blockchain technology is focused on its use in cryptocurrencies like Bitcoin. Blockchain technology is more than simply bitcoin it has a number of uses in business process management, government, banking, and finance. As a result, this paper makes an effort to look into and examine the possibilities and difficulties associated with present and potential Blockchain Technology implementations. As a result, several published research were thoroughly examined and assessed according to how they added to the body of knowledge on Blockchain.